2017
DOI: 10.1038/s41598-017-05487-7
|View full text |Cite
|
Sign up to set email alerts
|

TRIM21 is critical for survival of Toxoplasma gondii infection and localises to GBP-positive parasite vacuoles

Abstract: Interferon gamma (IFNγ) is the major proinflammatory cytokine conferring resistance to the intracellular vacuolar pathogen Toxoplasma gondii by inducing the destruction of the parasitophorous vacuole (PV). We previously identified TRIM21 as an IFNγ-driven E3 ubiquitin ligase mediating the deposition of ubiquitin around pathogen inclusions. Here, we show that TRIM21 knockout mice were highly susceptible to Toxoplasma infection, exhibiting decreased levels of serum inflammatory cytokines and higher parasite burd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
57
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(59 citation statements)
references
References 75 publications
(120 reference statements)
2
57
0
Order By: Relevance
“…with data from Foltz et al, 28 who identified TRIM21 as a critical factor in the defense against the obligate intracellular parasite Toxoplasma gondii. Furthermore, Trim21 À/À BMDMs were hyporesponsive to TLR2 stimulation by both the synthetic ligand PAM3CSK4 and M. bovis BCG, indicating that TRIM21 also plays an important role in response to more complex stimuli.…”
Section: Discussionmentioning
confidence: 64%
“…with data from Foltz et al, 28 who identified TRIM21 as a critical factor in the defense against the obligate intracellular parasite Toxoplasma gondii. Furthermore, Trim21 À/À BMDMs were hyporesponsive to TLR2 stimulation by both the synthetic ligand PAM3CSK4 and M. bovis BCG, indicating that TRIM21 also plays an important role in response to more complex stimuli.…”
Section: Discussionmentioning
confidence: 64%
“…12,15,21 It is, however, still not known how mGBPs specifically target the T. gondii PCV and distinguish it from other cell's membranes. For example, some studies suggest that TRAF6, p62, and TRIM21 are recruited to the T. gondii-containing vacuole, which favors its ubiquitination and might elicit p62-mediated recruitment of mGBP2, 26,27 whereas other studies argue that mGBP recruitment is p62-independent and PCV ubiquitination might be a consequence of mGBP-mediated vacuolar lysis. 28 In addition, it remains to be addressed how the GBP multimers destabilize the membrane of the PCV and of the parasite itself.…”
Section: Gbps In the Defense Against Protozoa And Virusesmentioning
confidence: 99%
“…Splenic NK cells were selected as, upon adoptive transfer, they have been shown to recirculate through all organs ordinarily containing NK cells 31. Previous studies showed that tachyzoites are detected in lymphoid tissues early after infection (between 2 and 6 days),4, 12, 32, 33 while parasites were detected in the brains of infected animals by 7 dpi 4, 8, 30, 34. We therefore decided to evaluate the parasite burden in the spleen and the brain of infected animals by PCR at 4 and 7 dpi.…”
Section: Resultsmentioning
confidence: 99%